2006
DOI: 10.1002/nbm.1025
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive processing, display and analysis for in vivo MR spectroscopic imaging

Abstract: Image reconstruction for magnetic resonance spectroscopic imaging (MRSI) requires specialized spatial and spectral data processing methods and benefits from the use of several sources of prior information that are not commonly available, including MRI-derived tissue segmentation, morphological analysis and spectral characteristics of the observed metabolites. In addition, incorporating information obtained from MRI data can enhance the display of low-resolution metabolite images and multiparametric and regiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
243
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(248 citation statements)
references
References 34 publications
5
243
0
Order By: Relevance
“…To document interindividual variation of the activation areas and to test whether a functional definition of Broca"s and Wernicke"s area had indeed been necessary, activation foci were determined in each subject in postprocessing and compared to the coordinates of a likely anatomically prescribed ROI (pars 8 opercularis and pars triangularis of the left inferior frontal gyrus for Broca"a area and the posterior section of the left superior temporal gyrus for Wernicke"s area) in native space. However from these areas no MRS data were acquired except if these overlapped with the functional definition.…”
Section: Roi Placement: Interindividual Differences In Location Of Acmentioning
confidence: 99%
See 1 more Smart Citation
“…To document interindividual variation of the activation areas and to test whether a functional definition of Broca"s and Wernicke"s area had indeed been necessary, activation foci were determined in each subject in postprocessing and compared to the coordinates of a likely anatomically prescribed ROI (pars 8 opercularis and pars triangularis of the left inferior frontal gyrus for Broca"a area and the posterior section of the left superior temporal gyrus for Wernicke"s area) in native space. However from these areas no MRS data were acquired except if these overlapped with the functional definition.…”
Section: Roi Placement: Interindividual Differences In Location Of Acmentioning
confidence: 99%
“…Furthermore, because most MRS studies use either single voxel (SV) localization techniques or spectroscopic imaging (SI) of single slices where the ROIs must be known and defined at the time of data acquisition, the functional definition of the ROI must usually precede MRS. Alternatively, spectroscopic whole brain analyses by multislice or 3D techniques [8], where ROIs can be chosen during data analysis, could be performed without knowledge of the exact region to be targeted, but these techniques are usually not considered to be as reliable and not as time-efficient for small focused ROIs, in particular when using short echo times. Since previous studies have shown dysfunctions in circumscribed cerebral areas related to the language system we investigated auditory verbal hallucinations (AVH) as a potential case of local limited metabolic imbalance.…”
Section: Introductionmentioning
confidence: 99%
“…Although MRSI allows mapping of the regional distribution of metabolites, the technique may not be suitable immediately for multi-center trials because of the longer acquisition times, the homogeneity issues with shimming larger volumes, the need to process and review hundreds of spectra, and the challenge of quantification. Despite these disadvantages, automated, fast 3D-MRSI software with whole brain coverage is under development and may be available in the future as a standardized package for routine use (Maudsley et al, 2006). Until then, there are many academic institutions that are already capable of providing the single-voxel spectroscopic set of data elements described previously for evaluation of TBI.…”
Section: Perfusion Imagingmentioning
confidence: 99%
“…Standard post-processing involves zero-filling, apodization using Gaussian or Lorentzian filtering, and Fourier transform of the free induction decay signal, as well as baseline and phase corrections [148][149][150][151].…”
Section: Proton Magnetic Resonance Spectroscopic Imagingmentioning
confidence: 99%